Censo populacional e avaliação da variabilidade genética das populações de mico-leão-preto (Leontopithecus chrysopygus Mikan, 1823) na Floresta Nacional de Capão Bonito- SP - Caldano, Lucas Tadeu Peloggia (2014)
The genus Leontopithecus consists of primate species with the largest size within the family Callitrichidae and their distribution is restricted to the remaining Brazilian Atlantic Forest. The black lion tamarin (Leontopithecus chrysopygus) is an endemic primate from the Atlantic Forest in the São Paulo state, and currently is critically endangered since his habitat has been significantly reduced to small areas of native forest. The destruction and fragmentation of its natural habitat and the reduction of food resources may increase the isolation among fragments and substantially raise the risk of species extinction due to loss of genetic variability and consequent reduction of its adaptive/evolutionary potential. It is of paramount importance to have an estimation of the current population minimum size, especially if a species is classified as endangered. Information about the abovementioned subject associated with genetic information could be used for the development of conservation strategies of the species. Therefore, we traversed all areas of potential habitat for the species within the Floresta Nacional de Capão Bonito-SP using a playback, counting the number of groups and of individuals per group in order to conduct a census in the area. It was identified 35 individuals at the end of the census, which were divided into seven groups. These animals were successfully capture 10 animals representing two groups of individuals, of which samples were taken for genetic studies. For genetic analysis microsatellite markers were used. Genetic diversity was low, revealing an average of 2.42 alleles. Kinship revealed that individuals in a group have no relation to another group. Although the absolute number of genetically analyzed is low, the results may be representative of the population of Floresta Nacional de Capão Bonito, considering the total population census. Thus, this work brings together information that contribute to increase the knowledge about genetic and ecological aspects of the black lion tamarin, which coupled with other studies can provide important information for the conservation of the species.